The impact of dehydration and rehydration on brewing yeast - Jenkins, David Martyn (2011)
In the brewing industry it is standard practice to propagate a pure yeast culture and inoculate (pitch) it into the fermentation vessel. Once fermentation is complete, yeast is recovered and reused in subsequent fermentations (known as serial repitching) until a decline in performance occurs or the required number of successive fermentations has been conducted. Propagation is currently required to initiate the entire process again, which requires additional equipment, energy, water inputs and time. It has long been proposed that Active Dried Yeast (ADY) offers an alternative method of yeast supply. Adoption of this innovation by the brewing industry has been low because of perceived issues with the fermentation performance of ADY, the availability of strains and hygiene concerns. In the current study the fermentation performance of ADY has been assessed with respect to viability, genomic stability, membrane integrity, yeast growth, attenuation, uptake of wort nutrients and aspects of flavour development. ADY requires rehydration before use and it has been demonstrated that viability is impaired in these slurries, though the extent of viability loss was dependent on strain and rehydration conditions. The source of cell death is unclear. Mitochondrial and genomic DNA integrity was assessed using a variety of techniques and shown to be unaffected by dehydration and rehydration. In contrast membrane integrity was affected. Changes in membrane fluidity, sterol content and fitness to perform could be detected in ADY. Performance of ADY in fermentation was also impaired. A lag in cell growth, attenuation and sugar and amino acid uptake were noted. Diacetyl formation occurred more rapidly and end fermentation diacetyl levels were higher for ADY. These differences were not maintained during serial repitching. It is proposed that ADY could be utilised to replace freshly propagated yeast, but direct addition to fermenters would require an improvement of performance during the first fermentation.